2022
DOI: 10.1021/acs.chemmater.2c02170
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metal Selection in the Radiation Stability of Isostructural M-UiO-66 Metal–Organic Frameworks

Abstract: Robust and versatile metal−organic frameworks (MOFs) have emerged as sophisticated scaffolds to meet the critical needs of the nuclear community, but their performance depends on their underexplored structural integrities in highradiation fields. The contributions of selected metal nodes in the radiation stability of MOFs within the isostructural M-UiO-66 series (where M = Zr, Ce, Hf, Th, and Pu; Zr-UiO-66 experiments were executed in a previous work) have been determined. Ce-, Hf-, and Th-UiO-66 MOF samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 93 publications
1
27
0
Order By: Relevance
“…A recent study pointed out that the Hf/Zr-based UiO-66 is highly resistant to direct γ-ray and He-ion irradiation. If the structural breakdown occurs in high-radiation fields, it would undergo a reduction in the surface area and crystallinity and a loss of the μ 3 -OH stretch . In this work, after over 100 kGy γ-ray irradiation in water, the characteristic peaks in the FT-IR spectra and the retention of its PXRD pattern demonstrated that all dispersed Hf/Zr/Ti-based UiO-66 moieties remained intact, and no H 2 or any other gas products were detected in irradiated dry UiO-66.…”
Section: Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A recent study pointed out that the Hf/Zr-based UiO-66 is highly resistant to direct γ-ray and He-ion irradiation. If the structural breakdown occurs in high-radiation fields, it would undergo a reduction in the surface area and crystallinity and a loss of the μ 3 -OH stretch . In this work, after over 100 kGy γ-ray irradiation in water, the characteristic peaks in the FT-IR spectra and the retention of its PXRD pattern demonstrated that all dispersed Hf/Zr/Ti-based UiO-66 moieties remained intact, and no H 2 or any other gas products were detected in irradiated dry UiO-66.…”
Section: Results and Discussionsupporting
confidence: 85%
“…If the structural breakdown occurs in high-radiation fields, it would undergo a reduction in the surface area and crystallinity and a loss of the μ 3 -OH stretch. 34 In this work, after over 100 kGy γray irradiation in water, the characteristic peaks in the FT-IR spectra and the retention of its PXRD pattern demonstrated that all dispersed Hf/Zr/Ti-based UiO-66 moieties remained intact, and no H 2 or any other gas products were detected in irradiated dry UiO-66. Only the porosity slightly increased with the accumulated absorbed dose possibly due to the impurity decomposition.…”
Section: ■ Results and Discussionmentioning
confidence: 52%
“…With the increasing irradiation dose, FWHM values of the two peaks fluctuate slightly (Figure b), indicating that the crystallinity is not largely weakened. N 2 adsorption–desorption isotherms at 77 K (Figure c) are also sensitive to detect structural damage after irradiation. After the 1000 kGy irradiation treatment, the BET specific surface area (270 m 2 g –1 ) is slightly lower than that of pristine IEF-11 (299 m 2 g –1 ) (Figure c), consistent with the results from the XRD pattern. In addition, FT-IR spectra (Figure d) show that after the 1000 kGy irradiation, the intensity and wavenumber of CO (1519 cm –1 ) and Ti–O–C (795 cm –1 ) signal peaks are highly consistent with those of the pristine sample.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This difference may be attributed to the following factors: (i) when the material is irradiated by β-rays, the loose coordination bond distribution of MIL-125 is easily activated and then the redox reaction occurs, leading to the breakage of coordination bonds. In contrast, the tight coordination bond arrangement (2D Ti−O−Ti arrangement) in IEF-11 can effectively disperse the energy of accepted electrons and maintain the integrity of the material framework; 32,36 (ii) the square acid ligand of IEF-11 has higher connectivity (Table S1), making its coordination bonds much more stable than MIL-125; 33 (iii) the metal node density of IEF-11 is lower than MIL-125 (Table S1), allowing it absorb to less radiation. 32,33 As concluded above, based on the tight coordination bonds and unique structure, IEF-11 possesses excellent irradiation resistance at the same irradiation dosage.…”
Section: Stability Analysismentioning
confidence: 99%
“…Conductive carbon materials derived from the pyrolysis of MOFs are often preferred for electrocatalysis 22,32,33 . In this study, the radiation-driven catalytic process requires that MOFs should sensitize the ionizing radiations and stabilize SAs while avoiding degradation 34,35 . In investigating possible support materials, we discovered UiO-66(Hf), one of the most easily accessible MOFs, exhibited quali ed radiation resistance and robust binding capacities for SAs, as well as presenting record-setting high probabilities of cascading secondary electron scattering 16,20 .…”
Section: Resultsmentioning
confidence: 99%